Relationship Between Gross Motor Function and Nutritional Status of Children with Cerebral Palsy-A cross-sectional study in a Tertiary Care Hospital of Bangladesh - Alam, Syeda Tabassum; Islam, Kazi Ashraful; Ahmed, Sanjida; Akhter, Shaheen; Kundu, Gopen Kumar; Fatema, Kanij; Tasneem, Ruhina; Begum, Momena; Akther, Mahboba; banu, Laila Arejuman; et al. (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Cerebral Palsy (CP) is one of the most common causes of chronic disability in children. Childhood malnutrition is a major public health issue in low- and middle-income countries. The gross motor function of children with CP can easily be assessed by the tool Gross Motor Function Classification System- Expanded &Revised (GMFCS-E&R). This study aimed to determine the relationship between GMFCS and nutritional status in children with cerebral palsy. Method: This cross-sectional observational study was conducted in the Department of Pediatric Neurology, IPNA, BSMMU from October 2019 to August 2020. All the patients aged 2-12 years were diagnosed as CP by clinical criteria and classified by GMFCS. Nutritional status (weight for age, height for age, weight for height, BMI) is assessed and classiﬁed according to the World Health Organization growth charts. Then linear and multinomial logistic regression methods to determine the associations between GMFCS and nutritional status. The correlation between motor function and nutritional status was assessed. Results: Among the 50 children 68% were male and 32% were female. The mean age of the CP children was 4.90±3.05 years. Most patients (66.0%) came from poor families followed by 24% from the middle class. Functionally majority of patients were in GMFCS level IV (28.0% ) and level V (20.0%). Maximum patients in spastic quadriplegia 42%, spastic hemiplegia 16%. The level of GMFCS was associated with nutritional status, as determined by anthropometry. Moderate and severe underweight significantly related with GMFC level IV and V. Moderate and severe stunted was significantly related with IV and V GMFC level. Moderate wasted was significantly related to GMFC levels III and IV. Mild malnutrition was significantly with GMFC level II and III. Severe malnutrition is significantly related to GMFC level IV and V. Conclusion: This study showed majority of cerebral palsy cases had severe functional gross motor disability and also severe grade of malnutrition. A significant association between severe grade of malnutrition and severe grade of motor disability was found. J Bangladesh Coll Phys Surg 2024; 42: 342-349